Implementation of Learning Management for Creating Early Childhood Independence Character - Rosnelli Rosnelli (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Research was conducted to find out learning management function to create the independent character of early childhood at school. The research was carried out in Preschool in Deli Serdang Regency, where the participants were 20 teachers. Data collection through observation, questionnaires and documentation was useful for strengthening the results of research data analysis. This type of research was quantitative descriptive analysis. The learning management functions that must be implemented in the learning process to create the independent character of early childhood in schools are: 1)designing learning, 2)implementing learning designs, 3)controlling the learning process and 4)evaluating learning outcomes. The research suggestion is the need for Preschool teacher training to come up with creative and innovative ideas through learning arts and cultural literacy for problem solving activities and providing challenges through the media of images to facilitate early childhood in an effort to create their independent character.